Nutrition and climate change: Shifting to sustainable healthy diets - Ruel, Marie T.; Fanzo, Jessica (International Food Policy Research Institute, 2022)
One of the most significant challenges for food systems today is ensuring that every individual has access to — and consumes — sustainable healthy diets. These are defined as nutritious, healthy (meaning they help prevent disease), safe, affordable, and culturally acceptable diets that support optimal nutrition and health and cause low environmental pressure and impact. The food systems tasked with producing these healthy diets are under significant stress due to environmental and natural resource constraints, as well as climate change. Moreover, the types and amounts of foods we consume — and the way we produce, process, and move these foods — compromise the stability and resilience of natural resources and biodiverse ecosystems and contribute to climate change.